The SAMI Galaxy Survey: the relationship between galaxy rotation and the motion of neighbours. Issue 1 (5th July 2022) - Mai, Yifan; Vaughan, Sam P; Croom, Scott M; van de Sande, Jesse; Barsanti, Stefania; Bland-Hawthorn, Joss; Brough, Sarah; Bryant, Julia J; Colless, Matthew; Goodwin, Michael; Groves, Brent; Konstantopoulos, Iraklis S; et al.
ABSTRACT: Using data from the SAMI Galaxy Survey, we investigate the correlation between the projected stellar kinematic spin vector of 1397 SAMI galaxies and the line-of-sight motion of their neighbouring galaxies. We calculate the luminosity-weighted mean velocity difference between SAMI galaxies and their neighbours in the direction perpendicular to the SAMI galaxies' angular momentum axes. The luminosity-weighted mean velocity offset between SAMI galaxies and neighbours, which indicates the signal of coherence between the rotation of the SAMI galaxies and the motion of neighbours, is 9.0 ± 5.4 km s −1 (1.7σ) for neighbours within 1 Mpc. In a large-scale analysis, we find that the average velocity offsets increase for neighbours out to 2 Mpc. However, the velocities are consistent with zero or negative for neighbours outside 3 Mpc. The negative signals for neighbours at a distance around 10 Mpc are also significant at the ∼2σ level, which indicate that the positive signals within 2 Mpc might come from the variance of large-scale structure. We also calculate average velocities of different subsamples, including galaxies in different regions of the sky, galaxies with different stellar masses, galaxy type, λRe, and inclination. Although subsamples of low-mass, high-mass, early-type, and low-spin galaxies show the 2–3σ signal of coherence for the neighbours within 2 Mpc, the results for different inclination subsamples and large-scale results suggest that the ∼2σ signals might result from coincidental scatter or variance of large-scale structure. Overall, the modest evidence of coherence signals for neighbouring galaxies within 2 Mpc needs to be confirmed by larger samples of observations and simulation studies.